2007
DOI: 10.1111/j.1525-1446.2007.00639.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of Maternal Chronic Disease and Negative Birth Outcomes in a Non‐Hispanic Black‐White Mississippi Birth Cohort

Abstract: Maternal chronic hypertension and diabetes were significantly associated with negative birth outcomes regardless of maternal race. Maternal cardiac disease was only significantly associated with PTB and LBW among African Americans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 20 publications
(15 reference statements)
3
26
0
Order By: Relevance
“…In agreement with the findings of Graham et al 26 , the results of the current study show that chronic maternal morbidities such as hypertension and cardiopathy were positively associated with low birth weight. Moreover, they show that morbidities characteristic of pregnancy (hypertension, preeclampsia, history of preterm, infectious diseases, premature rupture of membranes, and hemorrhages during pregnancy) are also risk factors for low birth weight 1,27 .…”
Section: Discussionsupporting
confidence: 82%
“…In agreement with the findings of Graham et al 26 , the results of the current study show that chronic maternal morbidities such as hypertension and cardiopathy were positively associated with low birth weight. Moreover, they show that morbidities characteristic of pregnancy (hypertension, preeclampsia, history of preterm, infectious diseases, premature rupture of membranes, and hemorrhages during pregnancy) are also risk factors for low birth weight 1,27 .…”
Section: Discussionsupporting
confidence: 82%
“…2,4,11 Our current findings are consistent with those of other studies demonstrating the deleterious pregnancy-specific effects of chronic hypertension. [6][7][8][9] These results demonstrate that adverse outcomes are increased even with mild BP elevation in treated or untreated women with chronic hypertension. Because women were randomized at 13-26 weeks of gestation, approximately 1 week after the preenrollment visit, the BPs correspond mainly to the midtrimester.…”
Section: Discussionmentioning
confidence: 91%
“…[1][2][3][4] It is associated with a threefold to fivefold increase in several adverse pregnancy outcomes including preeclampsia, small-for-gestational age (SGA) neonates, indicated preterm birth, placental abruption, and intrauterine fetal demise compared with pregnancies uncomplicated by chronic hypertension. [4][5][6][7][8][9] Although there is little debate that women with severe-range chronic hypertension (blood pressure [BP] 160/110 mm Hg or greater) should be treated, less is known regarding risks of mild-range chronic hypertension because some data suggest no increased risk in this range. 3,8 The American College of Obstetricians and Gynecologists and other organizations specifically recommend against starting or continuing antihypertensive therapy for mild chronic hypertension (140/90-159/109 mm Hg) because there is no evidence that therapy during pregnancy benefits the mother and there is concern that the risk of antihypertensive medication may impair placental perfusion and fetal growth.…”
Section: Level Of Evidence: IImentioning
confidence: 99%
“…This finding may represent compounded baseline obstetrical risks for older mothers, because these conditions increase with age (31,32), and are associated with adverse birth outcomes (33)(34)(35). In a review of more than 29,000 cases, Gilbert et al (36) found that chronic HTN significantly increased the risk of maternal and perinatal morbidity and mortality.…”
mentioning
confidence: 94%